A Kind of Discrete Variable Frequency Heavy-Load Soft Start System - Xiao Yi-ping (Institute of Advanced Engineering and Science, 2014)
A kind of discrete variable frequency heavy-load soft start system was designed in order to realize heavy-load soft starting of motor. It consisted of variable reactance converter, discrete variable frequency converter and controller. The system structure was described in detail and the principle of discrete variable frequency heavy-load soft starting was analyzed. Also the model of the system was made and simulation of the system was done. The simulation results proved that the system can not only start motor smoothly, but also increase the motor start torque greatly, thus heavy load soft-starting of motor can be realized perfectly. In addition, the experiment of the system was done. The experiment results proved that the simulation was correct and the designed discrete variable frequency heavy-load soft start system can realize heavy-load soft start of motor. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4930